2019
DOI: 10.3389/fmicb.2019.00420
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Biology of Lytic Bacteriophage vB_EaeM_φEap-3 Infecting Multidrug-Resistant Enterobacter aerogenes

Abstract: Carbapenem-resistant Enterobacter aerogenes strains are a major clinical problem because of the lack of effective alternative antibiotics. However, viruses that lyze bacteria, called bacteriophages, have potential therapeutic applications in the control of antibiotic-resistant bacteria. In the present study, a lytic bacteriophage specific for E. aerogenes isolates, designated vB_EaeM_φEap-3, was characterized. Based on transmission electron microscopy analysis, phage vB_EaeM_φEap-3 was classified as a member o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…In addition, the phage was also tested against reference strains of E. coli (MG1655), Acenitobacter baumannii, Enterobacter cloacae, Pseudomonas aeruginosa and Enterococcus faecalis. Spot assay was done as reported earlier (Zhao et al 2019 ). 300 µl of fresh bacterial culture was added to soft agar, overlaid on nutrient agar plate and allowed to solidify.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the phage was also tested against reference strains of E. coli (MG1655), Acenitobacter baumannii, Enterobacter cloacae, Pseudomonas aeruginosa and Enterococcus faecalis. Spot assay was done as reported earlier (Zhao et al 2019 ). 300 µl of fresh bacterial culture was added to soft agar, overlaid on nutrient agar plate and allowed to solidify.…”
Section: Methodsmentioning
confidence: 99%
“…One-step growth experiments were performed as described previously, with some modifications [ 50 ]. In brief, S. enterica strains S. Typhimurium 12, S. Typhimurium 13, S. Enteritidis 64, and S. Enteritidis 1392 were grown at given temperatures (25, 37, or 42 °C) until reaching OD 600 = 0.2.…”
Section: Methodsmentioning
confidence: 99%
“…The genome of phage P-KP2 is a linear double-stranded DNA that is comprised of 172,138 bp with a G + C content of 41.9%, and the termini of the phage genome is located at 38,590 bp (Supplementary Figure 2). Comparative analysis of the complete nucleotide sequence indicates that several phages show high similarity to P-KP2, including Enterobacter phage phiEap-3 (Zhao et al, 2019), Klebsiella phage Matisse (Provasek et al, 2015), Klebsiella phage KP27, Klebsiella phage KP15, Klebsiella phage PMBT1 (Koberg et al, 2017), Klebsiella phage KOX10, Klebsiella phage Miro (Mijalis et al, 2015), Escherichia phage phT4A (Pereira et al, 2017), and Klebsiella phage KOX8 (Table 1), which can be classified as a member of pseudo-Teven myophages which belong to "KP15likevirus" genus. Multiple genome alignment confirmed that these phages have parallel gene functional modules (Figure 3).…”
Section: Bioinformatics Analyses Of P-kp2 Genomementioning
confidence: 99%